Dlaczego w czasach jagiellońskich zanika w Polsce pieczęć majestatyczna? - Michał Knapik (Theatrum Historiae)
The article aims to introduce a new voice in the study of the disappearance of the majestic seal in the Polish sphragistic system in the second half of the fifteenth century. In researching this issue, the author places the symbolic meaning of the majestic seal and its use against the background of the political changes in the Poland of the Late Middle Ages and the visual representation of the kings of Poland and the royal rituals at the turn of the Middle Ages and the Early Modern era. According to the author, the disappearance of the Polish majestic seal was the result of the crisis and dispersion of royal majesty as a result of the final extinction of the Piast dynasty at the end of the fourteenth century.